Assessment of High-Risk Factors in Pregnancy and Their Association with Demographic Variables Among Women in Urban and Rural Communities of West Bengal. - Shreyasi Hui; Soma Das; Shubhra Chowdhury; Krishma Jindal; Divya (The Bioscan, 2026)
A descriptive study was conducted to assess the high-risk factors of pregnancy among women attending selected outpatient department of urban and rural community, West Bengal with the objectives to identify the high-risk factors of pregnancy and its association with selected demographic variables.